Utilization of Bidara Leaf Extract (Ziziphus mauritiana Lamk) as a Body Scrub For Skin Care - Agna Safira Yulia; Ratni Dewi; Nahar Nahar; Ratna Sari (Jurnal Teknologi, 2026)
Body scrub is a skincare product designed to exfoliate dead skin cells. Bidara leaf extract (Ziziphus mauritiana Lamk) was selected for its flavonoid, saponin, and tannin content, which contribute to antibacterial and antioxidant properties, while Epsom salt functions as an exfoliating agent that aids in dead skin removal and enhance skin regeneration. This study involved variations in bidara leaf extract concentration (0–5%) and Epsom salt concentration (10–50%). The formulations were evaluated through physical quality tests, including pH, homogeneity, adhesion, spreadability, organoleptic properties, antibacterial activity, and antioxidant activity. Results indicated that the formulation with 1% bidara leaf extract and 20% Epsom salt yielded the best outcomes, with a pH of 5.2 (compliant with SNI standards for topical preparations), good homogeneity, soft texture, and high panelist acceptance, particularly for sensitive skin. Antibacterial testing revealed the highest activity at 1% extract concentration, with an inhibition zone of 23 mm against Staphylococcus aureus. Antioxidant activity demonstrated free radical inhibition with an IC50 value of 18.94 µg/mL. These findings suggest that body scrub formulations incorporating bidara leaf extract and Epsom salt hold potential as natural, effective, and environmentally friendly skincare products.